2022
DOI: 10.1186/s13256-022-03443-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis during the recovery phase of dengue hemorrhagic fever: two case reports 

Abstract: Background Dengue fever is one of the most common tropical diseases, with high prevalence in many tropical countries including Sri Lanka. Dengue infection can present from subclinical infection to dengue shock syndrome. Further, the disease also shows a variety of atypical presentations and has been reported to mimic a number of causes of acute abdomen. Case presentation The authors report two children (a 6-year-old Tamil girl and an 8-year-old Mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Although case reports of acute appendicitis during acute DENV infection have been documented [ 13 , 39 , 56 , 57 ], our study found no significant increase in the risk of acute appendicitis in the first month or first year following DENV infection. However, we found a slightly increased risk of acute appendicitis after 1 year of DENV infection (aHR 1.32; P < 0.0001); the results remained statistically significant after adjusting for multiple comparisons, suggesting that the results were unlikely due to type 1 error.…”
Section: Discussioncontrasting
confidence: 82%
“…Although case reports of acute appendicitis during acute DENV infection have been documented [ 13 , 39 , 56 , 57 ], our study found no significant increase in the risk of acute appendicitis in the first month or first year following DENV infection. However, we found a slightly increased risk of acute appendicitis after 1 year of DENV infection (aHR 1.32; P < 0.0001); the results remained statistically significant after adjusting for multiple comparisons, suggesting that the results were unlikely due to type 1 error.…”
Section: Discussioncontrasting
confidence: 82%
“…According toThadchanamoorty, et al Dengue fever is a viral infection transmitted by mosquitoes and is recognized as a tropical disease that is often neglected by the World Health Organization (WHO), this condition has had a major impact on the Sri Lankan economy in providing primary and secondary health care over the past two decades. It has a myriad of clinical manifestations that range from self-resolving subclinical infection to fatal dengue shock syndrome, atypical presentation and multiorgan involvement recognized under the umbrella of expanded dengue syndrome in 2012 by WHO, various manifestations reported in expanded dengue syndrome, including cardiac involvement , brain, kidney, liver, spleen, pancreas, and gastrointestinal tract, complications that are not commonly reported are myocarditis, encephalitis, (Thadchanamoorthy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%